(untitled) (World Science, 2024)
The research has developed a technical solution for enhancing the core of polymer particles in the extruder with the modernization of the worm. The essence of the modernization of the worm lies in the fact that the mixing section of the worm has radial pins, which will ensure more efficient preparation of melted recycled material. This is the reason for the modernization of the worm with the increased mixing of the material and the efficiency of the production of polymeric particles with an extruder.